Assessing venous thrombus in renal cell carcinoma: preliminary results for unenhanced 3D-SSFP MRI. Issue 8 (August 2018) - Adams, L.C.; Ralla, B.; Engel, G.; Diederichs, G.; Hamm, B.; Busch, J.; Fuller, F.; Makowski, M.R.
Abstract : Aim: To test the potential of unenhanced cardiac- and respiratory-motion-corrected three-dimensional steady-state free precession (3D-SSFP) magnetic resonance imaging (MRI) for the assessment of inferior vena cava (IVC) thrombus in patients with clear-cell renal cell carcinoma (cRCC), compared to standard contrast-enhanced (CE)-MRI and CE-computed tomography (CT). Materials and methods: Eighteen patients with cRCC and IVC thrombus, who received CE-MRI and 3D-SSFP at 1.5 T between June 2015 and December 2017, were included. The diagnostic performance of 3D-SSFP in determining the level of thrombus extension, contrast-to-noise ratio (CNR), and image quality were compared with standard MRI/CT and validated against intraoperative and histopathology results. Results: There was 100% agreement between 3D-SSFP, 83.3% agreement between CE-MRI, and 71.4% agreement between CE-CT and surgical findings regarding the level of IVC thrombus. In addition, 3D-SSFP showed a slightly superior estimate of pathological IVC volume. 3D-SSFP reached a significantly higher CNR in the supra- and infrarenal IVC compared to the morphological sequence T2-weighted half-Fourier axial single-shot fast spin-echo (T2-HASTE) and all phases of CE-MRI. More specifically, 3D-SSFP showed a significantly higher CNR in the infrarenal IVC (mean CNR of 10.09±5.74 versus 4.21±2.33 in the delayed phase, p≤ 0.001) and in the suprarenal IVC (mean CNR of 9.22±4.11 versus 4.84±5.74 in the late arterial phase, p= 0.015). CE-CT also was significantly inferior to 3D-SSFP ( p≤ 0.01) and slightly inferior to CE-MRI ( p> 0.05). The thrombus delineation score for 3D-SSFP (4.38±0.67) was higher compared to CE-MRI (3.76±0.56, p= 0.005). Conclusion: This preliminary study indicates that 3D-SSFP can achieve an accurate assessment of IVC thrombus in cRCC patients without the need for contrast medium administration, being superior to standard MRI and CT. Highlights: D-SSFP enables visualization of IVC thrombus without the need for contrast agents. Appears superior to CE-MRI regarding the assessment of thrombus level. By use of 3D-SSFP quantitative and qualitative image quality can be improved. Excellent interobserver agreement suggests feasibility for clinical practise.